The Relationship of Husband's Support to the Improvement of Contraception Injection Acceptor in Puskesmas Segeri Kabupaten Pangkep - Ratna; Sumi, Susi Sastika (Journal of Humanities and Social Sciences (JHASS), 2020)
Perkembangan Pertumbuhan jumlah penduduk di dunia setiap tahun terus meningkat, keluarga berencana telah digambarkan sebagai alat yang kuat untuk mengurangi angka pertumbuhan jumlah penduduk, terutama dinegara-negara dengan tingkat pertumbuhan populasi yang tinggi dan prevalensi kontrasepsi yang rendah. Tujuan penelitian ini yaitu untuk mengetahui hubungan dukungan suami terhadap peningkatan akseptor KB suntik di Wilayah Kerja Puskesmas Segeri Kabupaten Pangkep. Penelitian ini menggunakan jenis penelitian kuantitatif dengan metode penelitian survey analytic dilakukan dengan rancangan cross sectional. Pengambilan sampel menggunakan teknik non-probability sampling yaitu purposive sampling dan jumlah sampel sebanyak 80 responden. Pengumpulan data menggunakan kuesioner. Data dianalisis menggunakan program SPSS dengan uji stastistik Chi-Squaredan tingkat kemaknaan ρ Value < 0,05. Berdasarkan hasil analisis hubungan dukungan suami terhadap peningkatan akseptor KB suntik diperoleh nilai ρ=0,037 berarti ada hubungan bermakna antara dukungan suami dengan peningkatan akseptor KB suntik. Kesimpulan dalam penelitian ini adalah terdapat hubungan dukungan suami terhadap peningkatan akseptor KB suntik di Wilayah Kerja Puskesmas Segeri Kabupaten Pangkep. Diharapkan adanya penginkatan edukasi kepada pasangan usia subur untuk ketepatan dalam pemilihan alat kontrasepsi. The Relationship of Husband's Support to the Improvement of Contraception Injection Acceptor in Puskesmas Segeri Kabupaten Pangkep Abstract: Growth in the world's population continues to increase every year, family planning has been described as a powerful tool to reduce population growth rates, especially in countries with high population growth rates and low contraceptive prevalence. The purpose of this study was to determine the relationship of husband's support to the increase in injecting family planning acceptors in the work area of Puskesmas Segeri Kabupaten Pangkep. This study uses quantitative research with analytic survey research methods conducted with cross sectional design. Sampling using non-probability sampling techniques, namely purposive sampling and a total sample of 80 respondents. Data collection using a questionnaire. Data were analyzed using the SPSS program with Chi-Squared statistical tests and the significance level ρ Value <0.05. Based on the analysis of the relationship between husband's support and the increase in injecting KB acceptors, the value ρ = 0.037 means that there is a significant relationship between husband support and an increase in injecting KB acceptors. The conclusion of this research is that there is a relationship between husband's support and the increase in injecting family planning acceptors in the work area of Puskesmas Segeri Kabupaten Pangkep. It is expected that there will be an increase in education for couples of childbearing age for accuracy in the selection of contraceptives. Keywords: Contraception Injection, Health, Husband Support.